Evaluating the impact of the teaching factory model on Vocational High School student competencies in the SMK Centre of excellence program - Tanjung Dahri; Syahwani Asty Khairi Inayah; Ayuningtyas Gilang; Sholihah Walidatush; Rivtryana Disya Ayu (BIO Web of Conferences)
The study analyzes the impact of the Teaching Factory learning model on enhancing Vocational High School (SMK) students’ competencies under the SMK Center of Excellence (SMK PK) Program. The model bridges education and industry by providing practice-based learning tailored to job market demands. Using a quantitative pre-test and post-test method combined with PLS-SEM, data was gathered through observations, questionnaires, and interviews with students, teachers, and industry partners. Results reveal a significant improvement in technical skills, work readiness, and soft skills, including problem-solving, teamwork, and discipline. Industry collaboration strengthened curriculum relevance and training quality, enhancing graduates' employability. Aligned with SDG 4 (quality education), the study highlights the model’s success in preparing students for the workforce and recommends its broader application to elevate vocational education competitiveness in Indonesia.